A Conceptual Model of Construct Ability in Construction Projects - Abdullah, Adam Abdelkarim (2000)
The concept of constructability enhances benefits to the owner; by provide the construction input at the earliest stage, i.e. during the conceptual planning stage. The present research aims to identify the common design- related problems and the factors that delay the design and construction processes (stage of detailed design and commencing of construction activities, etc.). A questionnaire survey was conducted; followed by interviews with construction personnel including contractors, project managers, designers, expert engineers, etc. The 'process complexity' was found to be the major factor that delayed the design and construction processes in the absence of construction input during the design phase. On the other hand, the main barrier to implement constructability was identified as the lack of construction experience of design organizations and the differences in contractual arrangement (the construction knowledge (Constructors) were not involved during project team meetings). This research also revealed that the integration of experienced construction personnel into the earliest stages of the prcject as full- fledged members of the project team and comprehensive tracking (analysis, retrieving and storing of the efficient, workable methods and procedures that can be implemented to the current and future project) will greatly improve the chances of achieving a better quality project. Making this perceive specific knowledge available to designers at the right time. It is also important to obtain information as an integrated environment. The Information Management Model has been proposed to address the problems surrounding the construction environment, such as contractual arrangement and team relationships. It is facilitates the recording of the intent behind construction project decisions. Thereby, provide a complete project history, to integrate construction participant's knowledge and experience into the planning and designs phases. This knowledge should be collected before and after the construction of a project, to make it available for the planning and design of future projects. Design/Build approaches, is being suggested by the study to apply during the preconstruction and through whole project. Moreover, specialized- formal constructability programming, and comprehensive tracking have been argued as an essential approaches during the planning and design phase.